Le criminel et l’autre : analyse des relations interpersonnelles de l’homme criminel - Fréchette, Marcel (Acta Criminologica)

(untitled) (Les Presses de l'Université de Montréal, 1970)
AbstractTHE CRIMINAL AND HIS RELATIONS WITH OTHERS : AN ANALYSIS OF INTERPERSONAL PROCESSESThis research is concerned with the problem of persistent criminal behaviour. An attempt is made to find its underlying causes and to identify characteristics which remain constant among all criminals. More specifically, these characteristics are looked for in the ways criminals communicate and interact with other people.The research uses the interpersonal conflict approach. A first hypothesis stipulates that the functions by which an individual relates to others are seriously damaged among criminals. Furthermore, the hypothesis of a precise genetic process involving the deterioration of the capacity to relate to others is formulated. A method of measurement is worked out and applied using the principles and the technique of Kelly's personal constructs theory.The study is a comparative one and is based on the differential approach. 214 subjects, of whom 121 are criminals and 93 well-adjusted, are tested. The measurement is aimed at the effectiveness of their perceptive reactions toward others. W^ith each group of criminals (recidivists, episodic criminals and juvenile delinquents), a control group is tested for purposes of comparison.The results are conclusive. At the root of persistent criminal behaviour, the presence of an incompatibility with others is confirmed. This manifests itself concretely in what is termed the feeling of interpersonal withdrawal. All the criminal groups tested show this feeling of withdrawal toward others. The nature and intensity of interpersonal failure is evaluated over three main areas of inter-action : relationship with others in general, relationship with the family of origin and relationship with antisocial peers.The study attempts to validate a new sociopathology characterizing individuals who have chosen to define themselves by continuous and serious « dissocialized » behaviour.